Management of anorexia prevents skeletal muscle wasting during cisplatin‐based chemotherapy for thoracic malignancies. Issue 1 (13th January 2020) - Miyawaki, Eriko; Naito, Tateaki; Nakashima, Kazuhisa; Miyawaki, Taichi; Mamesaya, Nobuaki; Kawamura, Takahisa; Kobayashi, Haruki; Omori, Shota; Wakuda, Kazushige; Ono, Akira; Kenmotsu, Hirotsugu; Murakami, Haruyasu; et al.
Abstract: Background: Cancer‐associated skeletal muscle loss often occurs in patients with advanced lung cancer who are receiving chemotherapy. This study aimed to elucidate the impact of chemotherapy‐induced nausea and vomiting (CINV) or anorexia on muscle wasting. Methods: In this post‐hoc analysis of a phase II clinical trial of antiemetic agents, chemotherapy‐naïve Japanese patients with thoracic malignancies were prospectively recruited between May and October 2015. Total control of CINV was defined as the absence of nausea and vomiting without rescue therapy 0–120 h after each course of chemotherapy. Non‐anorexia was defined as having no anorexia or having an anorexia grade no higher than '1' during the 3 month period following chemotherapy initiation. Skeletal muscle mass was measured by computed tomography, and lumbar skeletal muscle index (LSMI) was calculated. Results: Among 29 patients, CINV was totally controlled in 7 (24%) and grade 2 or 3 anorexia was observed in 10 (34%). The LSMI significantly decreased across the entire cohort (mean ± standard error of the mean: −3.1 ± 0.6 cm 2 /m 2, P  < 0.01); this reduction was similar among patients with and without total control of CINV (−4.1 ± 1.3 vs. −2.8 ± 0.7 cm 2 /m 2, P  = 0.38). Patients with anorexia experienced a larger decrease in LSMI than did those without anorexia during the study period (−5.4 ± 0.9 vs. −1.9 ± 0.7 cm 2 /m 2, P  < 0.01). Conclusions: Significant skeletal muscle mass depletion was observed despite well‐controlled CINV. Continuous oral food intake may be required throughout the course of cisplatin‐based chemotherapy.